Tales from the global economy greenspan alert - Newson, Jeremy; British Broadcasting Corporation ([S.l.] : BBC Active, 2006)
This program looks through finance, economics and politics to see the human face of the global economy. Explores the governmnt economist of US, look through perspective of famous economist, Alan Greenspan and discovers environment of working with news and market on CNN studio
Title from title screen
Executive producer, Gina Newson ; editor, Alana Smith ; sound, Tom Bergen...[et al.] ; camera, Stan Staniski...[et al.]
Keywords: Greenspan, Alan, -- 1926-; Government economists -- United States; Monetary policy -- United States; United States -- Economic policy